Biomechanical evaluation of porous titanium implants (CpTi) fabricated by powder technology - Mohammed, Dhuha h; Alnakkash, Widad AH (Journal of Baghdad College of Dentistry, 2015)
Background: It may be an important prospective clinical use of manufacturing of porous implant for clinical situations, such as cases of limitation in bone height, low bone density .The small segment of porous implant an effective osseointegration allows increasing in contact area provided for small segmented porous provided by its surface configuration. This study was done to Fabricate porous titanium implants by powder technology, as well as the observation of removal torque values of porous titanium implants compared to smooth titanium implants.Materials and methods: Twenty porous titanium implants (3.2mm in diameter and 8mm in length) were manufactured by powder technology using commercially pure titanium powder of ≤75um particles size, with polyvinyl alcohol powder of 212-300um particle size, as a space holder, by volume ratio (70:30) % respectively. The mixed powder was compacted using punch and die set -specially designed for this study –under 20 bar then sintering at 900 ºC by the use of argon gas. Twenty smooth titanium implants were prepared of (3.2mm in diameter and 8mm in length) by lathing of commercially pure titanium rod as a control group. The implants were examined by X-ray diffraction (XRD) and scanning electron microscope (SEM), as well as estimation of porosity percentage. For each tibia of the 20 white New Zealand rabbits, one implant of each type (one porous in right, and the smooth in left tibia), were inserted through surgical procedure carried under serial condition. Mechanical test was performed to evaluate the bone-implant interface, after (2 and 6 weeks) healing periods . Results: Porous implants were obtained successfully by powder technology with 52% porosity and pore size 210um 17±. The porous implant showed significantly higher removal torque values when compared to smooth implants at the two different intervals of examination (2,6 weeks) , this proved to be statistically highly significant, also a highly significant difference was noticed for the means of the torque removal values in the same group at different implantation , with no evidence of clinical features of inflammatory reaction with both .Conclusions: Powder technology seemed to be particularly advantageous in fabrication of porous titanium. Porous implant show an increasing bone ingrowth compared with the smooth type represented by higher removal torque for both healing periods (2, 6) weeks .Key words: Porous titanium implant, powder technology, removal torque test.